An Assessment of Milkfish Marketing in Semarang Regency, Central Java, Indonesia - Mudiantono (1985)
The milkfish (Chanos chanos ) is one of the fishes best suited for culture in brackish water ponds. The culture of milkfish has been practised for several hundred years in Indonesia, particularly in Java island. At present , milkfish has become a popular food fish in Indonesia , especially in Java, and a major portion of them is marketed fresh, while the rest is marketed as processed milkfish. This study evaluates the efficiency in marketing of milkfish in Semarang Regency, Central Java, Indonesia in terms of various significant dimensions such as market competition, market integration and marketing margin. The structure conduct- performance of the market approach is used to measure the marketing efficiency. This approach was developed in the United States as a way to analyze the market organization of the industrial sector, but is was later applied in the agricultural sector. Results of analyses show that the market is efficient, although there are some considerations what should be noted. The market is at least consistent with competitive behaviour, except at the wholesale level. The degree of market integration coefficients is high as indicated by high correlation among county/municipality prices which also implies the existence of pricing efficiency in the markets. Marketing margin anal y s i s indicates that producer's share from the retail price is high and profit margins to the wholesalers and retailers are reasonable. Yet, the marketing system harbours significant flaws particularly credit-tie and unfair tactics which somewhat deny the producers the full benefit of a competitive market. It a p pears that properly-managed producers cooperatives would be able to offer a fair and efficient marketing services to the producers.